19‐5L: Late‐News Paper: Perceptually Optimized Dual‐layer Light Field 3D Display Using a Moiré‐aware Compressive Factorization. Issue 1 (May 2016) - Liao, Wenjuan; Wang, Shizheng; Sun, Mingyu; Surman, Phil; Zheng, Yuanjin; Yuan, Junsong; Sun, Xiao Wei
Abstract : In this paper we propose a rotation angle‐based perceptual optimization framework for dual‐layer light field 3D displays. The whole framework flow can be divided into two phases; first, the moiré pattern is simulated based on the rotation angle and a moiré cost for visual perception is calculated and second, the moiré cost is further incorporated into the final optimization of the proposed compressive factorization for the light field 3D display. In this way, a moiré‐aware compressive factorization with rotation optimization is proposed to generate the final display content for our prototype. Experiments demonstrate that the proposed method provides a promising perceptual optimization in both moiré mitigation and definition enhancement for the visual perception of compressive light field displays.